Financial technologies in Ukraine’s banks: features and prospects of development - Nakonechna, Olena; Mykhailyk, Olga (My University, 2022)
The article is devoted to the study of the global banking market of FinTech and current trends in international investment in FinTech companies. The study presents the analyses of the banking FinTech-market of Ukraine and its main segments in which Ukrainian banks operate. Modern fintech products of cooperation between Ukrainian banks and fintech companies are presented. The factors that contributed to the emergence of Fintech have been identified, as well as their features for the Ukrainian market. For further promotion and identifying prospects of banking business development SWOT analysis was made and was formed the adaptation scheme of introducing FinTech innovations into banking. The main trends in FinTech industry development are also identified, which should be taken into account when forming key factors of banking sector transformation to implement the new Ukrainian banking business models and indicated positive factors for the introduction of new financial services and products. Стаття присвячена дослідженню світового банківського ринку FinTech та сучасних тенденцій міжнародного інвестування у FinTech компанії. У дослідженні представлено аналіз банківського FinTech-ринку України та його основних сегментів, в яких працюють українські банки. Представлені сучасні фінтех-продукти співпраці українських банків і фінтех-компаній. Виявлено фактори, що сприяли появі Fintech, а також їх особливості для українського ринку. Для подальшого просування та визначення перспектив розвитку банківського бізнесу проведено SWOT-аналіз та сформовано схему адаптації впровадження FinTech інновацій у банківську діяльність. Також визначено основні тренди розвитку FinTech галузі, які необхідно враховувати при формуванні ключових факторів трансформації банківського сектору для впровадження нових українських банківських бізнес-моделей та вказано позитивні фактори для впровадження нових фінансових послуг і продуктів.
Keywords: фінтех; fintech; фінтех-компанії; fintech companies; банк; bank; фінансові послуги; fintech services; цифровий банкінг; digital Banking; відкритий банкінг; open Banking; блокчейн; blockchain; кафедра економіки і права